Return To The Idea of A Central Communication Hub For Poland - Arkadiusz WROZEK (Communications of International Proceedings, 2025)
The development of the modern economy is contingent upon an efficient and effective transportation system, sustained by a robust economy that ensures the necessary volume of goods, passengers, and services to cover operational costs and infrastructure expansion. Given the rapid growth of the aviation market and the increasing competition among airports in Central and Eastern Europe, Poland has revisited the concept of constructing a central airport, referred to as the Central Communication Port (CPK). The emergence of low-cost carriers led to the dispersion of air traffic across smaller regional airports in Poland, diminishing the significance of Warsaw's central airport. However, the expansion of LOT Polish Airlines has facilitated the reconsolidation of passenger traffic at Warsaw Airport, attracting travelers from Poland and other Central European countries while connecting Europe with Asia, North America, and the Middle East. The increasing air traffic has resulted in operational inefficiencies at Warsaw Airport, necessitating the revival of the plan to construct a new central airport in Poland. To comprehensively examine this issue, this study sets forth research objectives aimed at determining whether the construction of a central airport is feasible and aligns with the demands of the aviation market in Poland and Europe. A supplementary objective involves analyzing competitive factors affecting airports and airlines in Central and Eastern Europe. The research methodology encompasses a literature review and source criticism, along with a comparative analysis of the Polish hub airport project and airports in Vienna, Zurich, Helsinki, and Copenhagen. The handling capacity and passenger services of the new central communication port in Poland present an opportunity to attract global aviation players from America and Asia, fostering the development of new logistics chains. Despite the high investment risk, with appropriate transport policies and effective airport management strategies, the long-term prospects for this investment remain promising. The evolving European transportation system, with the Central Communication Port as its integral component, represents a significant research area, wherein studies on operational principles, efficiency, and passenger and cargo management will become the foundation of future scientific inquiry.
Keywords: air hub; aviation policy; airport management